2018
DOI: 10.1021/acsmacrolett.8b00275
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Manipulation of Supramolecular Structures of Giant Molecules via Macromolecular Composition and Sequence

Abstract: We have successfully synthesized a series of monodispersed chain-like giant molecules with precisely controlled macromolecular composition and sequence based on polyhedral oligomeric silsesquioxane (POSS) nanoparticles using an orthogonal “click” strategy. Their nonspherical supramolecular structures, such as lamellae, double gyroids, and hexagonal packed cylinders, are mainly determined by the composition (namely, the number of incorporated amphiphilic nanoparticles). In addition, by precisely alternating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…It was found that sequence does impact the phase‐separated nanostructures significantly. For example, the DB 6 , BDB 4 , and B 2 DB 3 form three distinct spherical phases, that is, body–center–cubic (BCC), sigma (σ), and A15, respectively . “Folding” of the chain and the resulting distinct interfacial curvature were believed to account for such differences.…”
Section: Sequence‐isomersmentioning
confidence: 99%
“…It was found that sequence does impact the phase‐separated nanostructures significantly. For example, the DB 6 , BDB 4 , and B 2 DB 3 form three distinct spherical phases, that is, body–center–cubic (BCC), sigma (σ), and A15, respectively . “Folding” of the chain and the resulting distinct interfacial curvature were believed to account for such differences.…”
Section: Sequence‐isomersmentioning
confidence: 99%
“…Click adaptors are a class of small molecules that easily convert one click functionality to another or extend the total number of clickable sites. For instance, isomeric chain‐like giant molecules have been precisely synthesized through an orthogonal click strategy that combined SPAAC and oxime ligation reactions (Figure b) . Taking advantage of the introduction of two growing sites from the click adaptor, half as many reaction cycles are needed for a given number of POSS cages along the chain, offering new opportunities to study sequence effects of those giant molecules in nonspherical phase regions.…”
Section: Synthetic Strategy For Poss‐hybrid Polymers With Well‐definementioning
confidence: 99%
“…a) Linear sequence‐mandated giant molecules via repeated esterification reaction cycles from two different types of clickable POSS, b) sequence of isomeric chain‐like giant molecules synthesized from POSS with two clickable functionalities and “linear click adaptor” by combining SPAAC and oxime ligation, c) iterative synthetic strategy for POSS‐based sequence isomers (PS‐(APOSS)(BPOSS) 2 by SPACC from azido‐terminated PS, and two different types of clickable POSS. Reproduced with permission . Copyright 2017, Wiley‐VCH, American Chemical Society; Copyright 2016, Royal Society of Chemistry.…”
Section: Synthetic Strategy For Poss‐hybrid Polymers With Well‐definementioning
confidence: 99%
“…Cheng and coworkers have produced a series of famous and important works starting from 2010 on POSS amphiphilic materials and their assemblies [ 26 , 81 , 82 , 83 ]. Recently, they found that difference between phase-separated nanostructures could be determined by precisely controlling the sequence and the number of incorporated POSS cages (composition), because the sequence of the symmetry could affect the cross-sectional areas of the hydrophobic/hydrophilic POSS domains [ 84 ]. In another work, they also found that both the compositional variation and specific sequences could induce unconventional phase formation from specifically designed chain-like giant molecules.…”
Section: Mechanisms Of Self-assembly Of Poss-based Amphiphilic Copmentioning
confidence: 99%